Effect of Primary Salt in the Kinetic Study of Oxidation of Schiff Base of Aryl Amines and Salicylaldehyde by Ce4+ - K. Bane, Varsha; P. Fulwadhva, Usha; R. Shah, Chetan; S. Dodwad, Suresh; M. Shaikh, Manzoor (Asian Journal of Chemistry, 2010)
Kinetic studies on the oxidation of Schiff bases have been made using ceric sulphate as an oxidant in the absence and presence of inert KCl with varying concentrations. The reaction showed first order kinetics. Primary salt effect has been shown to be valid for the reaction studied.